2020
DOI: 10.3390/cancers12092578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Target Location, Size, and Patient Age on Normal Tissue Sparing- Proton and Photon Therapy in Paediatric Brain Tumour Patient-Specific Approach

Abstract: Background: Proton radiotherapy produces superior dose distributions compared to photon radiotherapy, reducing side effects. Differences between the two modalities are not fully quantified in paediatric patients for various intracranial tumour sites or age. Understanding these differences may help clinicians estimate the benefit and improve referral across available centres. Our aim was to compare intensity-modulated proton therapy (IMPT) and intensity-modulated photon radiotherapy (IMRT) radiation doses for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…However, long-term follow-up in clinical practice is necessary to evaluate the advantages of PBT for reducing the rates of adverse events and second cancer. SR-1.2: Intracranial local irradiation [11][12][13][14][15][16][17][18][19][90][91][92][93] All the studies examined in this chapter showed that PBT decreased the radiation dose in organs at risk, in comparison with X-ray therapy. Furthermore, three studies predicted that these decreased doses reduced late adverse events.…”
Section: General Remarksmentioning
confidence: 89%
“…However, long-term follow-up in clinical practice is necessary to evaluate the advantages of PBT for reducing the rates of adverse events and second cancer. SR-1.2: Intracranial local irradiation [11][12][13][14][15][16][17][18][19][90][91][92][93] All the studies examined in this chapter showed that PBT decreased the radiation dose in organs at risk, in comparison with X-ray therapy. Furthermore, three studies predicted that these decreased doses reduced late adverse events.…”
Section: General Remarksmentioning
confidence: 89%
“…Recognition of the importance of assessing and minimizing pituitary dose, as well as other organs at risk, has led to the development of specific guidelines for delineation, and it is now a common practice to outline the pituitary gland as an organ at risk when contouring CNS and H&N radiotherapy. 11 Evidence on the exact tolerance dose of the pituitary gland is limited and the target pituitary dose constraint and level at which screening for pituitary insufficiency should occur is quite wide ranging but generally at least 20 Gy. [11][12][13] The Pediatric Normal Tissue Effects in the Clinic 20 international collaboration acknowledges there are a number of hurdles to surmount in exploring and defining normal tissue tolerances in developing children, including inadequate patient-level dosimetry for relevant organs at risk; our cohort provides relevant information on this in relation to pituitary gland dose received and subsequent pituitary insufficiency and suggests that we should be aiming for as low a dose as possible as the only dose band that was found to carry no risk was <10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Evidence on the exact tolerance dose of the pituitary gland is limited and the target pituitary dose constraint and level at which screening for pituitary insufficiency should occur is quite wide ranging but generally at least 20 Gy. [11][12][13] The Pediatric Normal Tissue Effects in the Clinic 20 international collaboration acknowledges there are a number of hurdles to surmount in exploring and defining normal tissue tolerances in developing children, including inadequate patient-level dosimetry for relevant organs at risk; our cohort provides relevant information on this in relation to pituitary gland dose received and subsequent pituitary insufficiency and suggests that we should be aiming for as low a dose as possible as the only dose band that was found to carry no risk was <10 Gy. Even at lower prescribed doses, the risk of pituitary insufficiency remains significant as demonstrated by over 30% of patients in this cohort developing GHD with doses <20 Gy and TSHD with doses of 20-29 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work by the authors, six de‐identified cranial CT datasets and respective OAR contours of pediatric patients were sourced from St. Jude Children's Research Hospital 25 . Ethics approval was obtained from St. Jude Children's Research Hospital and University of South Australia, ethics code: 202267.…”
Section: Methodsmentioning
confidence: 99%